High‐Temperature Electrical Conductivity of LaCr1−xCoxO3 Ceramics. Issue 3 (13th December 2015) - Bonet, Alexander; to Baben, Moritz; Travitzky, Nahum; Greil, Peter
Abstract : LaCr1− x Co x O3 solid‐solution ceramics ( x = 0.0–0.3) were prepared by pressureless sintering of a submicrometer powder. The powder was synthesized by a modified glycine nitrate process at 800°C. The electrical conductivity of the material sintered at 1600°C was measured by AC four‐wire method from room temperature to 1200°C. While undoped ( x = 0) LaCrO3 revealed semiconductivity dominated by thermally activated mobility of small polarons over a vast temperature range, substitution of Co for Cr gave rise for a pronounced enhancement of conductivity at temperatures >200°C. XPS analysis showed that the concentration of Cr 4+ on the Cr‐site and Co 2+ at the Co‐site increased with Co substitution suggesting a thermally activated redox reaction Cr 3+ + Co 3+ →Cr 4+ + Co 2+ to create additional charge carriers. Thus, Co doping offers a high potential for designing the electrical conductivity making LaCr1− x Co x O3 an interesting resistivity material for high temperature applications.